Pengembangan Video Gaya Antarmolekul Berbasis Multipel Representasi untuk Mengatasi Miskonsepsi - Fera Apriliani*; Erlina Erlina; Husna Amalya Melati; Rody Putra Sartika; Ira Lestari (Universitas Syiah Kuala, 2022)
Intermolecular forces are one of the topics in basic chemistry. Intermolecular forces consist of abstract concepts that require multiple representations (macroscopic, submicroscopic, and symbolic) to visualize those concepts. Moreover, the multiple representations are needed to help students understand the abstract concepts of intermolecular forces. Multiple representations were presented as pictures, diagrams, and animation in the videos. The aims of this research are to develop a video of intermolecular forces based on multiple representations and to determine the level of validity and student’s responses to the video. This study employs the 4D method formulated by Thiagarajan which consist of 4 stages. However, this study only adopted 3 stages; define (to know the problem), design (manufacture of product to solve the problem), and development (to determine the level of validity and student responses). The instruments used in this study were the validity and the response questionnaires. Data collected were then analyzed using the percentage criteria proposed by Riduwan. The video provides the conceps and real-life example of the London forces and hydrogen bonding. Video validation shows the level of subject matter validity is 95,38%, media validity is 98,89%, and language validity is 91,11%, where all the aspects were very valid criteria. Every aspect is validated by 3 experts. Student responses on a limited scale by 7 students show a percentage of 87,8% and a large scale by 20 students of 88,9% with very good criteria. Based on the result, the video can be used in the study of intermolecular forces